2014
DOI: 10.1089/brain.2014.0254
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Stimulation Increases Functional Connectivity of Basal Forebrain-Paralimbic Network in Isoflurane-Anesthetized Rats

Abstract: Brain states and cognitive-behavioral functions are precisely controlled by subcortical neuromodulatory networks. Manipulating key components of the ascending arousal system (AAS), via deep-brain stimulation, may help facilitate global arousal in anesthetized animals. Here we test the hypothesis that electrical stimulation of the oral part of the pontine reticular nucleus (PnO) under light isoflurane anesthesia, associated with loss of consciousness, leads to cortical desynchronization and specific changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 109 publications
1
8
0
Order By: Relevance
“…The stimulation increased cortical spike rates, diminished slow-frequency power, and re-instated higher-frequency power. Our studies are consistent with rodent studies that have shown recovery of consciousness and awake-like cortical dynamics after stimulation in a variety of brain regions (Pillay et al, 2014;Solt et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The stimulation increased cortical spike rates, diminished slow-frequency power, and re-instated higher-frequency power. Our studies are consistent with rodent studies that have shown recovery of consciousness and awake-like cortical dynamics after stimulation in a variety of brain regions (Pillay et al, 2014;Solt et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple drug infusion studies have solidified its role as a sleep regulatory region (Lopez-Rodriguez et al 1994;Bourgin et al 1995;Marks and Birabil 1998;Ahnaou et al 1999). More recently, stimulation of the PnO has been shown to induce cortical desynchronization in lightly anesthetized rats as well as increase functional connectivity to basal forebrain-paralimbic structures such as the nucleus basalis of Meynert (Pillay et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While therapeutic electrodes have been implanted in infratentorial targets very near PnO in humans, such as the pedunculopontine nucleus (Mazzone et al 2005;Plaha and Gill 2005), a supratentorial target may offer a decreased surgical risk profile. Of note, the nucleus basalis is supratentorial, is in the ascending projection pathway of PnO, and has widespread cholinergic and noncholinergic arousal connections with the neocortex Pillay et al 2014;Motelow et al 2015) making it a promising potential future target for stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, 6 adult, male, Sprague-Dawley rats were scanned during light and deep sedation with propofol at 20 or 40 mg/kg/h equivalent to conscious sedation and unconsciousness [10,12]; the order of doses was reversed in consecutive experiments. The animals’ lungs were artificially ventilated; arterial blood pressure, heart rate, arterial oxygen saturation, core temperature, respiratory rate, inspired and expired oxygen and carbon-dioxide concentrations were continuously monitored.…”
Section: Methodsmentioning
confidence: 99%
“…From all sliding windows, a common subset of voxels with ReHo values exceeding the threshold of mean + 2 standard deviations (SD) was defined as the region of interest. This threshold was previously found optimal to delineate functionally connected regions of the brain with all voxels present at both anesthetic concentrations [10,12]. …”
Section: Methodsmentioning
confidence: 99%